Follow‐up of patients subjected to direct and indirect pulp capping of young permanent teeth. A retrospective study - Carmen Llena; Miriam Hernández; Maria Melo; José Luis Sanz; Leopoldo Forner (Wiley, 2021)
Abstract Objective A retrospective study of the success rate of direct pulp capping (DPC) and indirect pulp capping (IPC) was carried out in children between 6-14 years‐old, considering separately primary caries or caries affecting teeth with molar incisor hypomineralization (MIH). Material and methods Data were collected in a dental public health service. Following the inclusion criteria, 232 treatments were analyzed. Success was defined by the presence of a functional tooth without clinical signs or symptoms of pulpal or periapical disease. The success rate was correlated to patient gender, the affected tooth and the indication of therapy using the chi‐squared and Fisher exact test. The success time related to treatment type was evaluated through the Mann-Whitney test. Results The IPC and DPC success rate was 99.4%, and 84.6%, respectively (p = .01). Success was significantly lower when caries affected teeth with MIH than when caries affected teeth without MIH (p = .01). The mean survival for DPC and IPC was 14.07 ± 1.30 and 15.98 ± 0.80 months, respectively (p = .07). Conclusions When caries were located in teeth that were not affected by MIH, IPC was significantly more successful than DPC, but did not differ significantly when caries were placed in teeth with MIH. Key points Minimally invasive therapy is a successful approach for decayed young permanent teeth. The success of IPC was greater than the success of DPC wen caries was placed in teeth not affected by MIH. In teeth not affected by MIH the success of DPC or IPC did not differ significantly.